Peran Kepemimpinan dalam Lembaga Pendidikan Islam - Monalisa, Febri Nanda; Fadla, Sarah Lailatil; Hayati, Fitri; Puri, Eliza (Lembaga Yasin AlSys, 2022)
The purpose of this study was to determine the role of leadership in Islamic educational institutions. This research is a library research with a qualitative research method approach. The results of this study indicate that leadership styles include: democratic leadership style; delegative leadership styles, bureaucratic leadership styles, laissez faire leadership styles authoritarian leadership style: charismatic leadership styles. The main function of educational leaders, among others, is that leaders help create brotherhood, cooperation, with a full sense of freedom, leaders help groups to organize themselves, namely participate in providing stimulation and assistance to groups in setting and explaining goals. The leadership role in the educational institution is devided into; 1) as an educator, 2) as a manager, 3) as an administrator4) as a supervisor, 5) as a leader, 6) as s reformer, and 7) as a motivator.